Metabolic Effects of the Very-Low-Carbohydrate Diets: Misunderstood "Villains" of Human Metabolism - Manninen Anssi H (Taylor & Francis Group, 2004)
Abstract During very low carbohydrate intake, the regulated and controlled production of ketone bodies causes a harmless physiological state known as dietary ketosis. Ketone bodies flow from the liver to extra-hepatic tissues (e.g., brain) for use as a fuel; this spares glucose metabolism via a mechanism similar to the sparing of glucose by oxidation of fatty acids as an alternative fuel. In comparison with glucose, the ketone bodies are actually a very good respiratory fuel. Indeed, there is no clear requirement for dietary carbohydrates for human adults. Interestingly, the effects of ketone body metabolism suggest that mild ketosis may offer therapeutic potential in a variety of different common and rare disease states. Also, the recent landmark study showed that a very-low-carbohydrate diet resulted in a significant reduction in fat mass and a concomitant increase in lean body mass in normal-weight men. Contrary to popular belief, insulin is not needed for glucose uptake and utilization in man. Finally, both muscle fat and carbohydrate burn in an amino acid flame.